2001
DOI: 10.1029/2000gl012381
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray imaging of the solar wind—Mars interaction

Abstract: Abstract.Wherever the solar wind meets a neutral atmosphere, X-rays are emitted by charge-exchange processes between heavy solar wind ions and the neutrals. Using an empirical model of the proton flow near Mars we present computer simulations of X-ray emissions from this chargeexchange process in Mars' exosphere. We also discuss implications for remote sensing. Here we show that the total X-ray luminosity near Mars from charge-exchange is greater than 10 2s eV/s for typical solar wind conditions. This flux is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 14 publications
7
34
2
Order By: Relevance
“…If we also adjust to the average slow SW ion abundances, then our simulated luminosity can reach between 1.2 and 2.0 MW, which brings us to almost perfect agreement with previous simulations (Krasnopolsky 2000;Holmström et al 2001;Gunell et al 2004), but still a far way from the observed values.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…If we also adjust to the average slow SW ion abundances, then our simulated luminosity can reach between 1.2 and 2.0 MW, which brings us to almost perfect agreement with previous simulations (Krasnopolsky 2000;Holmström et al 2001;Gunell et al 2004), but still a far way from the observed values.…”
Section: Discussionsupporting
confidence: 69%
“…Previous simulations from Holmström et al (2001) with similar SW conditions (V sw = 400 km s −1 , n sw = 2.5 cm −3 ) yielded 2.4 MW (1.52 × 10 25 eV/s) for solar minimum and 1.5 MW (0.93 × 10 25 eV/s) for solar maximum conditions of the neutral coronas, within a 10 R M radius. On the other hand, Gunell et al (2004) find 1.8 MW for a 6 R M simulation box (with V sw = 330 km s −1 , n sw = 4.4 cm −3 inputs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the result of numerical simulations (Holmström et al 2001, Plate 1), which predicted a crescent-like structure that resembles (on a smaller scale) the observed emission in ionized carbon (Fig. 7f).…”
Section: Fig 8 A) Superposition Of the Rgs Images Inmentioning
confidence: 99%
“…The geometry of the solar wind flow around the ionospheric obstacles of these nonmagnetized planets resembles that around the Earth's magnetosphere. In 2001 the Chandra X-ray observatory detected an X-ray halo due to solar wind charge exchange around Mars [Gunell et al, 2004;Holmström et al, 2001]. In 2006 and 2007, Chandra observations also revealed that the Venusian exosphere emits solar wind charge exchange soft X-rays [Dennerl, 2008].…”
Section: Imaging the Magnetospherementioning
confidence: 99%